2019
DOI: 10.21580/dms.2018.182.3259
|View full text |Cite
|
Sign up to set email alerts
|

DST (Digital Storytelling) to Familiarize ‘Stop Bullying’ Cases among Elementary School Aged-Children

Abstract: <p>This article discusses about the use of DST as a way to introduce children to the concept of bullying cases among students. As a participatory action research, this research aims to educate students as young learners to aspect of bullying. The term of DST has been increasingly used by scholars to illustrate various forms of support of learning to help young learners learn successfully. Children in the DST creation process enjoyed the stages. It was revelaed that culturally bullying has already being t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…Salah satu bentuk perlindungan yaitu mendasari pada Undang-Undang Nomor 35 tahun 2014 mengenai perlindungan anak di Indonesia (Analiya & Arifin, 2022). Pendekatan ini ditempuh dengan berbagai cara, seperti penyuluhan (Limilia & Prihandini, 2019) penggunaan media edukasi berupa motion graphics untuk meningkatkan toleransi antar siswa (Savitri et al, 2018), media animasi (Mirnayenti et al, 2015), digital storytelling (Puspitasari et al, 2019), dan film (Cahyaningrum et al, 2018). Pencegahan perundungan juga banyak dilakukan secara verbal dengan skrining dan edukasi pencegahan melalui focus group discussion (Amalia et al, 2019), dan pemberian lagu (Widyaningrum, 2018).…”
Section: Pendahuluanunclassified
“…Salah satu bentuk perlindungan yaitu mendasari pada Undang-Undang Nomor 35 tahun 2014 mengenai perlindungan anak di Indonesia (Analiya & Arifin, 2022). Pendekatan ini ditempuh dengan berbagai cara, seperti penyuluhan (Limilia & Prihandini, 2019) penggunaan media edukasi berupa motion graphics untuk meningkatkan toleransi antar siswa (Savitri et al, 2018), media animasi (Mirnayenti et al, 2015), digital storytelling (Puspitasari et al, 2019), dan film (Cahyaningrum et al, 2018). Pencegahan perundungan juga banyak dilakukan secara verbal dengan skrining dan edukasi pencegahan melalui focus group discussion (Amalia et al, 2019), dan pemberian lagu (Widyaningrum, 2018).…”
Section: Pendahuluanunclassified
“…This technology advancement helps in the learning process. Further, Puspitasari et al (2018) reported the use of technology integrated into the learning English process to provide bullying literacy.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, the teacher can feelthe use of digital media is very helpful and speeds up the process of delivering material more efficiently and attractively because in the current era the integration of technology in learning is needed,innovation in the use of digital electronic media is a reflection of technology integration into the learning process (Aeni & Yusupa, 2018;Fahmi et al, 2021).This is also supported by previous research which found that the delivery of material or information in learning through digital media is very enjoyable for students so that it can increase active participation in the learning process (Yeni & Cagiltay., 2017). Previous research found that bullying that occurs can be prevented through several approaches, namely animation media (Swearer & Hymel, 2015), with motion graphics media to increase tolerance among students (Hanif, 2020), DST media Digital Story Telling (Puspitasari, 2018)and film media (Cahyaningrum et al, 2018).…”
Section: Introductionmentioning
confidence: 99%